2019
DOI: 10.3389/fphys.2019.00327
|View full text |Cite
|
Sign up to set email alerts
|

Gliclazide Prevents 5-FU-Induced Oral Mucositis by Reducing Oxidative Stress, Inflammation, and P-Selectin Adhesion Molecules

Abstract: Oral mucositis (OM) is one of the main side effects of the head and neck cancer treatment, particularly radiotherapy and/or chemotherapy. OM is characterized by ulcers, erythema, dysphagia, xerostomia, and increased susceptibility to opportunistic infections. In the perspective of finding pharmacological therapies to prevent inflammation and ulceration of OM, the investigation of the pleiotropic effect of commercial drugs is needed, among them gliclazide, an antidiabetic drug. This study aimed to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…This is because neutrophils secrete a repertoire of proteases and enzymes such as MMPs, elastase, Cathepsin G, and MPO that damage tissue (61,62). MPO is abundantly expressed in neutrophil granules and is associated with severe OM lesions (45,63) and delayed wound healing (64). Neutrophils also produce various MMPs, such as MMP-9, which was detected at elevated levels in Il17ra −/− mice, and is associated with tissue destruction during periodontal disease and OM (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…This is because neutrophils secrete a repertoire of proteases and enzymes such as MMPs, elastase, Cathepsin G, and MPO that damage tissue (61,62). MPO is abundantly expressed in neutrophil granules and is associated with severe OM lesions (45,63) and delayed wound healing (64). Neutrophils also produce various MMPs, such as MMP-9, which was detected at elevated levels in Il17ra −/− mice, and is associated with tissue destruction during periodontal disease and OM (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…This research was approved by the Ethics Committee on the Use of Animals of the Federal University of Rio Grande do Norte (CEUA-UFRN), permit number 002001/2017. The experimental OM model was induced in golden Syrian hamsters ( Mesocricetus auratus ) males weighing 180 g. They were maintained with rations, water ad libitum, at a temperature of 22 ± 2 °C, and a light/dark cycle of 12 h [ 15 , 36 ]. OM was induced by two intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…The goals of mucositis management are to prevent or reduce the severity of toxicity and to manage the associated symptoms, which will, in turn, enable the continued delivery of cancer therapy without interruption or dose reduction and improve the overall prognosis [ 13 ]. Previous research has shown that drugs with anti-inflammatory action can prevent OM [ 14 , 15 , 16 , 17 ]. Recently, it was shown that dexamethasone (DEX) ameliorated OM induced by 5-FU [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thalidomide, an NF-κB inhibitor, significantly improved mucosal tissue in irradiated mice, although the underlying mechanism still requires further study ( 63 ). Other drugs, such as amiforstine and gliclazide, reduce oxidative stress and inflammation ( 64 , 65 ). Growth factors and cytokines are also used to treat radiation mucositis.…”
Section: Clinical Intervention For Riom and Malnutrition In Hnc Patiementioning
confidence: 99%